Manajemen Pendidikan Karakter Siswa dalam Menumbuhkan Moderasi Beragama di SMK Nurul Huda Peleyan Kapongan Situbondo - Rusdianah Rusdianah; Farida Ulvi Na’imah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The importance of the leadership of the madrasa head in developing a religious culture in Madrasah Aliyah Nurul Huda al-Banat Situbondo. This leadership aims to develop the religious culture that exists in the madrasa environment.The aims of this study are 1) to describe the management of student character education in fostering religious moderation. 2) to describe the implementation of the attitude of religious moderation. The type of research used is qualitative research with a case study approach. Data collection techniques by means of observation, interviews, and documentation. The data analysis technique used in this qualitative research has four stages, namely data collection, data reduction, data presentation, drawing conclusions and suggestions. Meanwhile, in looking for the validity or validity of the data using data triangulation techniques. The results of this study are the management of student character education in fostering religious moderation is carried out by 1) through intracurricular activities 2) through co-curricular activities 3) through extracurricular activities. While the implementation of character values in fostering religious moderation is with the teacher being a good role model and role model in terms of tolerance, honesty, cooperation, responsibility and unity.